2003
DOI: 10.1002/clc.4960260409
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of serial QT dispersion in patients with first non‐Q‐wave myocardial infarction: Relation to the severity of underlying coronary artery disease

Abstract: Background: Increased QT dispersion (QTD) has been correlated with ventricular arrhythmias. Recent reports suggest that it may serve as a marker of the severity of underlying coronary artery disease (CAD). Hypothesis: The aim of this study was to examine in‐hospital changes of QTD and their possible correlation with the severity of underlying CAD in patients with first non‐Q‐wave myocardial infarction. Methods: In 62 patients we estimated QTD, precordial QTD, as well as their values corrected for heart rate on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…It is well known that the QT interval on standard 12-lead ECG is sensitive to myocardial ischaemia. Several studies have reported a relationship between increased QTc dispersion and CAD (28,29) . It has been known that ischaemic attacks lead to a temporary increase in QTcd in patients diagnosed with CAD (30) .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that the QT interval on standard 12-lead ECG is sensitive to myocardial ischaemia. Several studies have reported a relationship between increased QTc dispersion and CAD (28,29) . It has been known that ischaemic attacks lead to a temporary increase in QTcd in patients diagnosed with CAD (30) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown previously that in patients with first non-Q-wave myocardial infarction, prolongation of QTd correlated with the severity of underlying CAD designated by the Duke Myocardial Jeopardy Score. 24 However, when atrial pacing was used during angiography, prolongation of QTd during stress positively correlated with severity of stenosis. 25,26 This discrepancy could be attributable to the difference in patient characteristics.…”
Section: Discussionmentioning
confidence: 99%